2010
DOI: 10.1590/s0066-782x2010005000040
|View full text |Cite
|
Sign up to set email alerts
|

Monitorização ambulatorial da pressão arterial em pacientes normotensos com hipotireoidismo subclínico

Abstract: Background: Overt hypothyroidism is associated with elevation of diastolic blood pressure; however the association of subclinical hypothyroidism (SH) with arterial blood pressure (ABP) alteration is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
2
3
0
2
Order By: Relevance
“…This result is in accordance with the hypothesis that SCH leads to atherosclerosis by augmenting classical CV risk factors such as dyslipidaemia and systemic hypertension (6). Indeed, positive correlations between serum TSH and blood pressure (35,36) and between TSH and serum lipids (2, 37, 38) have been demonstrated in several studies. In addition, a potential relationship between SCH and metabolic syndrome and a reduction in insulin sensitivity have also been proposed (39,40), and SCH also seems to be associated with additional CV risk factors.…”
Section: Discussionsupporting
confidence: 89%
“…This result is in accordance with the hypothesis that SCH leads to atherosclerosis by augmenting classical CV risk factors such as dyslipidaemia and systemic hypertension (6). Indeed, positive correlations between serum TSH and blood pressure (35,36) and between TSH and serum lipids (2, 37, 38) have been demonstrated in several studies. In addition, a potential relationship between SCH and metabolic syndrome and a reduction in insulin sensitivity have also been proposed (39,40), and SCH also seems to be associated with additional CV risk factors.…”
Section: Discussionsupporting
confidence: 89%
“…The analyses were exploratory, and findings should be confirmed for subjects in different districts and for different populations of subjects. In addition, the observed indicators in our study were relationships between thyroid function and clinic blood pressure, others studies had shown both overt and subclinical hypothyroidism were not only associated with the clinic blood pressure but also related to ambulatory blood pressure [28][29][30]. To the best of our knowledge, few studies have been performed to examine the relationship of blood pressure to thyroid function in children and adolescents.…”
Section: Discussionsupporting
confidence: 61%
“…Additionally, we evaluated the effect of Hy on blood pressure, since thyroid dysfunction is associated with alterations in the systolic and/or diastolic pressures 4,18,31 . The measurements showed a higher SBP in the HG.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, most studies have focused on the abnormalities of cardiac and blood vessel function in the presence of hypo and hyperthyroidism (Hy). In general, TH increase basal metabolism and oxygen consumption acting directly on the heart and blood vessels 1-4 . Clinical and experimental evaluation are often based on the demonstration of an increase in myocardial contractility and heart rate (HR) on the one side and reduced peripheral vascular total resistance (PVTR) followed by a decrease in cardiac efficiency in the long run on the other side.…”
Section: Introdutionmentioning
confidence: 99%